Pengembangan Kecerdasan Emosi dan Spiritual Menuju Insan Kamil Perspektif Ary Ginanjar Agustian - Dewi Agustriani; Linda Auliyatul Fauziyah (Happiness: Journal of Psychology and Islamic Science, 2022)
Ary Ginanjar Agustian's thoughts on ESQ try to collaborate between emotional intelligence (EQ) and spiritual intelligence (SQ), through the core of Islamic teachings, namely ihsan, the six pillars of faith and the five pillars of Islam as an alternative point of view in bringing modern humans to human dignity. This study aims to describe the philosophical perspective of human beings and the concept of ESQ WAY 165 by Ary Ginanjar Agustian, as well as analyze the development of emotional and spiritual intelligence towards human beings in the perspective of Ary Ginanjar Agustian. This research uses the library method. The research data that has been obtained is then analyzed using text analysis and content analysis type discourse. The results of further research are presented descriptively so that the presentation is clear and detailed. Based on the results of the research, the following conclusions can be drawn: 1) From a philosophical perspective, human beings can be obtained through the process of tajalli and taraqqi; 2) The concept of ESQ WAY 165 Ary Ginanjar Agustian is the right method to maintain human Divine traits which are located in the God Spot, so that they can be well maintained, as well as a stronghold of the emotional dimension (EQ) so that they always have reliable mental resilience and are always in stable condition; 3) The development of emotional and spiritual intelligence by Ary Ginanjar Agustian is carried out to guide humans towards being perfect, namely by means of; clear the heart, build mentality, and carry out worship in the pillars of Islam